Analysis of peculiarities of identification, diagnostics and course of tuberculosis in patients with tuberculosis/HIV co-infection - V. P. Melnyk; T. H. Khursa; Ya. О. Yakymova; G. Ya. Soloninka (Zaporožskij Medicinskij Žurnal)
Objective – to analyse dynamics of detection of tuberculosis and HIV/AIDS in tuberculosis/HIV co-infection, to identify the main clinical forms of tuberculosis, the type of tuberculosis process and the structure of incidence of tuberculosis, to analyse dependence of a clinical form of tuberculosis on quantity of CD4 cells.